VIRA OU DEIXA – UM RECURSO EDUCACIONAL DIGITAL PARA O ENSINO FUNDAMENTAL - SOARES, CARINE G. T.; EICKHOFF, FERNANDO; PEREIRA, JULIANE S.; MORAES, DONIA R. D. M. D.; PEREIRA, TÂNIA M.; PORTELLA, ZENI M. S. (Salão do Conhecimento, 2013)
Resumo